2020
DOI: 10.3389/fphys.2020.00928
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Osteopontin Is a Marker of Advanced Heart Failure and Cardiac Allograft Vasculopathy: Evidence From Transplant and Retransplant Hearts

Abstract: Background Heart transplant is the gold standard therapy for patients with advanced heart failure. Over 5,500 heart transplants are performed every year worldwide. Cardiac allograft vasculopathy (CAV) is a common complication post-heart transplant which reduces survival and often necessitates heart retransplantation. Post-transplant follow-up requires serial coronary angiography and endomyocardial biopsy (EMB) for CAV and allograft rejection screening, respectively; both of which are invasive proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Elevated OPN level on day 0 and 7th after KTx was associated with the lower probability of rejection-free survival and was an independent predictor of AR Alchi et al ( 2005 ) Yes OPN expression in kidney biopsies of patients with AR was high and correlated with elevated interstitial monocytes infiltration, and inflammation Rouschop et al ( 2006 ) Yes/No Renal OPN and CD44 expression was higher in KTx patients with AR than in non-rejecting group and correlated with the degree of interstitial inflammation. Soluble CD44 plasma concentration was higher in rejecting than in non-rejecting patients; however, soluble OPN plasma level was similar in both groups Mansour et al ( 2021 ) No Elevated urine OPN level and OPN expression in kidney donors was associated with lower risk of delayed graft function and graft failure HTx Schipper et al ( 2011 ) Yes OPN plasma level was higher in patients with heart failure than in healthy controls and decreased after HTx Irion et al ( 2020 ) Yes OPN expression in cardiac tissue of patients with CAV who received retransplantation was high LTx Cabiati et al ( 2017 ) Yes OPN plasma level and OPN expression in liver tissue of patients with HCV-positive HCC undergoing LTx was higher than in healthy controls and correlated with thrombin, 7 s-collagen and Notch-1. A significant reduction of OPN plasma levels was observed at 6 months after LTx Sieghart et al ( 2011 ) Yes OPN expression in HCC patients undergoing LTx was high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated OPN level on day 0 and 7th after KTx was associated with the lower probability of rejection-free survival and was an independent predictor of AR Alchi et al ( 2005 ) Yes OPN expression in kidney biopsies of patients with AR was high and correlated with elevated interstitial monocytes infiltration, and inflammation Rouschop et al ( 2006 ) Yes/No Renal OPN and CD44 expression was higher in KTx patients with AR than in non-rejecting group and correlated with the degree of interstitial inflammation. Soluble CD44 plasma concentration was higher in rejecting than in non-rejecting patients; however, soluble OPN plasma level was similar in both groups Mansour et al ( 2021 ) No Elevated urine OPN level and OPN expression in kidney donors was associated with lower risk of delayed graft function and graft failure HTx Schipper et al ( 2011 ) Yes OPN plasma level was higher in patients with heart failure than in healthy controls and decreased after HTx Irion et al ( 2020 ) Yes OPN expression in cardiac tissue of patients with CAV who received retransplantation was high LTx Cabiati et al ( 2017 ) Yes OPN plasma level and OPN expression in liver tissue of patients with HCV-positive HCC undergoing LTx was higher than in healthy controls and correlated with thrombin, 7 s-collagen and Notch-1. A significant reduction of OPN plasma levels was observed at 6 months after LTx Sieghart et al ( 2011 ) Yes OPN expression in HCC patients undergoing LTx was high.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that OPN plasma concentration after HTx decreased significantly to levels observed in the control group. In another study Irion et al ( 2020 ) analyzed the expression of nuclear OPN in cardiac tissue from 20 heart transplant patients receiving retransplantation. Moreover, the number of cells (including cardiomyocytes and non-cardiomyocytes) with nuclear OPN has been evaluated.…”
Section: Opn In Heart Transplantationmentioning
confidence: 99%
“…To investigate the expression of SGLT-2 in paraffin-embedded renal (or cardiac) sections, immunofluorescence imaging was performed on kidneys from all groups as previously described [ 78 ]. Sections from kidneys were incubated for 45 min at 70 degrees, dewaxed with xylene washes and hydrated by graded ethanol washes of 100% (twice for 3 min), 95%, 80% and 70% followed by water immersion (twice for 4 min).…”
Section: Methodsmentioning
confidence: 99%
“…Aside from advances in imaging, there has been a concurrent search for biomarkers associated with CAV for early detection and as potential treatment targets. These include osteopontin, a pro-inflammatory cytokine that correlates with severe CAV [39]; endothelin-1, a vasoconstrictor peptide associated with accelerated CAV development [40]; and various microRNAs [41][42][43], among others [44][45][46][47][48]. These markers still require prospective validation to assess their utility in CAV detection, as well as continued evaluation as possible treatment targets.…”
Section: Cardiac Allograft Vasculopathy Detectionmentioning
confidence: 99%